2020
DOI: 10.1177/1524839920963691
|View full text |Cite
|
Sign up to set email alerts
|

Local and State Policy Action Taken in the United States to Address the Emergence of E-Cigarettes and Vaping: A Scoping Review of Literature

Abstract: Introduction In response to rising rates of youth vaping and e-cigarette use, states and localities in the United States have adopted various tobacco control policies and have extended their utility to these emerging products. However, the extent to which these policies have been evaluated for their impact on youth use is unknown. Method Two databases (PubMed, Google Scholar) were searched for English language peer-reviewed articles pertaining to electronic cigarette policy evaluation between 2009 and 2020. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…To address the research gaps identified above and improve comparability between studies, we suggest developing a standardised approach, including common questions. Rigorous evaluation of policies aimed at limiting youth EC access would provide a robust basis for future policy development [ 41 , 62 ]. For instance, better knowledge of how national legislation (e.g., T21 measures), flavour restrictions, and public education campaigns have contributed to decreases in EC use among US youth could identify opportunities to strengthen existing measures [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…To address the research gaps identified above and improve comparability between studies, we suggest developing a standardised approach, including common questions. Rigorous evaluation of policies aimed at limiting youth EC access would provide a robust basis for future policy development [ 41 , 62 ]. For instance, better knowledge of how national legislation (e.g., T21 measures), flavour restrictions, and public education campaigns have contributed to decreases in EC use among US youth could identify opportunities to strengthen existing measures [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the trajectory of the relationship between smoking and e-cigarette use is critical to ensure the development of appropriate policy related to e-cigarette use. For example, a recent review suggested that US policies related to e-cigarette use tend to be modelled on tobacco control strategies (e.g., age restriction to reduce retail access, taxation) and are reactionary to industry tactics for promotion (e.g., flavour restrictions; [21]). If e-cigarettes increase uptake of later smoking behaviours, then using tobacco control strategies as a model is warranted to minimise possible harm.…”
Section: Why Is Directionality Important?mentioning
confidence: 99%
“…Policymakers could develop regulations to enforce more strict advertising policies explicitly prohibiting the promotion of vaping products, including restrictions on content that indirectly promotes vaping [99,100].…”
Section: Implications For Policy and Researchmentioning
confidence: 99%